Performance study between variable refrigerant flow and chilled water air conditioning system / Muhamad Nurshafiq Mohd Yunos - Muhamad Nurshafiq , Mohd Yunos (2019)
Currently, the world been a witnessed on how the evolution of air conditioning industries takes place. From an idea of centrifugal water chiller by Willis Carrier back in 1921, today we can see how the chiller industry have booming the market. The variety of chiller was introduce and to the latest there are a modular chiller system and a chiller that been installed with a variable speed drive technology in a way to increase the chiller performance itself. On top of that, despite the chiller system, there is another air conditioning system that has captured the attention of this industry. The system known as Variable Refrigerant Flow. The concept of this system was basically connecting a single or modular outdoor system to a number of indoor system. Currently, Hitachi variable refrigerant flow system has taken the lead in producing it most efficient variable refrigerant flow system in the market. The competition among the air condition brand in Malaysia is very competitive since Malaysia has the highest demand in air conditioning units. Due to this fact, the study towards the performance of this two type of system was done. Throughout the study, variable refrigerant flow system has offer the lowest equipment cost to be compared with chiller, but this system generate higher operational cost. This due to instability of the refrigerant charge throughout the system. Using water as a primary source of refrigerant is the best idea since it can be control precisely rather than other refrigerant such as in this case is R410A which is used for variable refrigerant flow system. This also led to a result that chiller give higher coefficient of performance if to be compared with variable refrigerant floe system.